2021
DOI: 10.35451/jkk.v4i1.855
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Minuman Kurma Terhadap Peningkatan Hemoglobin Pada Ibu Hamil Penderita Anemia Di Rumah Sakit Grandmed Lubuk Pakam

Abstract: Anemia is a disease associated with pregnant women. The incidence of anemia due to iron mineral deficiency. This studi aims to determine the effect of giving dates drink to increasing haemoglobin levels in pregnant women with anemia in Rumah Sakit Grandmed Lubuk Pakam. This research method is quasi experiment with pre and posttest design. The population in this study is pregnant women with anemia in Rumah Sakit Grandmed Lubuk Pakam. The sample is 38 people consisting. In the treatment group was given intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In line with research conducted by Raini that found date palm juice can increase hemoglobin levels in pregnant women, this is supported by Natasha’s theory that hemoglobin forming factors such as Fe, B 12 , and folic acid are all found in dates. 12 However, it must be noted that the iron content in dates, as much as 0.90 mg, is not sufficient to meet the iron needs of pregnant women if it is not accompanied by regular consumption of Fe tablets.…”
Section: Discussionmentioning
confidence: 99%
“…In line with research conducted by Raini that found date palm juice can increase hemoglobin levels in pregnant women, this is supported by Natasha’s theory that hemoglobin forming factors such as Fe, B 12 , and folic acid are all found in dates. 12 However, it must be noted that the iron content in dates, as much as 0.90 mg, is not sufficient to meet the iron needs of pregnant women if it is not accompanied by regular consumption of Fe tablets.…”
Section: Discussionmentioning
confidence: 99%